Pengaruh Lingkungan Kerja, Disiplin Kerja, dan Motivasi Kerja terhadap Kinerja Guru Madrasah Ibtidaiyah Negeri Kabupaten Bireuen: The Influence of Work Environment, Work Discipline, and Work Motivation on the Performance of State Islamic Elementary School (Madrasah Ibtidaiyah Negeri) Teachers in Bireuen Regency - Maghfiratunnafis Maghfiratunnafis; Marwan Marwan; Hera Yanti (ITScience (Information Technology and Science), 2026)
Teacher performance is a crucial factor in improving the quality of education. This study aims to examine the influence of the work environment, work discipline, and work motivation on teacher performance at State Islamic Elementary Schools (Madrasah Ibtidaiyah Negeri/MIN) in Bireuen Regency. A quantitative approach employing a survey method was applied in this research. The population consisted of 143 teachers from six MIN schools in Bireuen Regency. A sample of 105 respondents was determined using the Slovin formula with a 5% margin of error. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS. Partially, the work environment had a positive and significant effect on teacher performance (Sig. = 0.013). Work discipline also had a positive and significant effect (t = 6.258; Sig. = 0.000) and was identified as the most dominant variable. Likewise, work motivation had a positive and significant effect on teacher performance (t = 5.176; Sig. = 0.000). Simultaneously, the three independent variables had a positive and significant effect on teacher performance (F = 45.648; Sig. = 0.000), with a coefficient of determination (R²) of 0.576, indicating that 57.6% of the variation in teacher performance was explained by the model, while the remaining 42.4% was influenced by other factors not examined in this study. The findings indicate that the work environment, work discipline, and work motivation play significant roles in enhancing the performance of MIN teachers in Bireuen Regency. Therefore, school administrators and policymakers should improve the quality of the work environment, strengthen work discipline, and enhance teachers' work motivation to support better teacher performance and improve the overall quality of education.